Die bemagtiging van die armes - Vester, P. (Faculty of Theology, University of the Free State, 2000)
The issue addressed in this article is whether the poor can be empowered to change their own situation without becoming revolutionary. Poverty comprises lack of the most basic life-sustaining goods. However, the poor as people before God, can be empowered to change their situation. Although poverty is an all-inclusive problem, the possibility of helping the poor to realise that they are called to take possession of their own destiny is important. In Jesus Christ a new way of hope and change is offered. With the realisation of their own situation comes the responsibility to become involved. By means of an important ministry the poor should be helped to regain self-respect and to act accordingly. Initiatives on the part of the poor are therefore of the utmost importance.
Keywords: Poverty; Christianity